Fabrication, characterization, and evaluation of a novel nano-ATP/chitosan membranes scaffold for bone regeneration - Linxiang Zhang; Ting Dai; Xiaoyu Wu; Bin Yi; Hongbin Zhao (Journal of Applied Biomaterials & Functional Materials)
Guided tissue regeneration/guided bone regeneration membranes (GTR/GBR) are widely used to repair damaged bone, manufactured using various materials, including synthetic polymers, natural polymers, metals, and inorganic compounds. Our previous study showed that nano-attapulgite (nano-ATP) composite membranes could significantly increase bone regeneration. Here, the porous nano-ATP-incorporated CH membranes were fabricated via the technique of freeze gelation (FG). The property and thermal stability of membranes were tested by scanning electron microscopy (SEM), Fourier-transform infrared spectroscopy (FTIR), and thermogravimetric analysis (TGA). Cell proliferation and morphology on the membranes were also studied. In vivo Micro-CT and histological analyses were used to evaluate new bone formation in rat cranium defect models. The results indicated that with increasing ATP content, the water absorption, porosity, swelling rate, and degradation rate of chitosan membranes significantly decreased; conversely, the thermal weight loss and mechanical strength exhibited a marked increase. Culture of mouse mesenchymal cells (D1) showed that ATP-incorporated membranes increased cell proliferation and matrix deposition. Furthermore, the results from Micro-CT and histological staining demonstrated that ATP-incorporated membranes could increase new bone formation. These results suggest that this novel nano-ATP incorporated membrane has great potential for bone tissue engineering applications and may lead to effective bone regeneration and repair.